2019
DOI: 10.3390/polym11010156
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PVDF/Hyperbranched-Nano-Palygorskite Composite Membrane for Efficient Removal of Heavy Metal Ions

Abstract: In this work, three kinds of hyperbranched polyamidoamine-palygorskite (PAMAM-Pal) were designed and synthesized by grafting the first generation polyamidoamine (G1.0 PAMAM), G2.0 PAMAM and G3.0 PAMAM onto Pal surfaces, respectively. Then, these PAMAM-Pals were used as additives to prepare polyvinylidene fluoride (PVDF)/hyperbranched polyamidoamine-palygorskite bicomponent composite membranes. The structures of the composite membranes were characterized by Fourier transform infrared spectroscopy (FTIR), thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Considering their high-affinity interaction with heavy metal ions, PAMAM dendrimers were used to modify membrane materials and improved their adsorption capacity [ 82 , 83 , 84 , 85 ]. With PDVF as a raw substrate, Kotte et al reported a one-pot method for the preparation of a new family of mixed matrix PVDF membranes with in situ synthesized PAMAM dendrimers [ 83 ].…”
Section: Adsorbents Of Different Substratesmentioning
confidence: 99%
“…Considering their high-affinity interaction with heavy metal ions, PAMAM dendrimers were used to modify membrane materials and improved their adsorption capacity [ 82 , 83 , 84 , 85 ]. With PDVF as a raw substrate, Kotte et al reported a one-pot method for the preparation of a new family of mixed matrix PVDF membranes with in situ synthesized PAMAM dendrimers [ 83 ].…”
Section: Adsorbents Of Different Substratesmentioning
confidence: 99%
“…Metal, zeolite and carbon based nanosorbent are commonly applied adsorbent for water purification. For the adsorptional removal of HMIs different types of adsorbent like humic acid [87], activated carbons [88], bio-chars, sawdust [89], coal ash [90], resin [91], carbon nanotubes [92], graphene oxide [93], zeolites [94], bio-chars [95], sepiolites [96], palygorskite [97], mesoporous materials [98], and layered double hydroxides (LDHs) [99] were reported for heavy metal ion removal. A broad range of nano-adsorbents based on polyaniline (PANI) and its derivatives also appeared as promising candidate for the removal of heavy metals form polluted water [100].…”
Section: Nanohybrids For Adsorptional Removal Of Organic Pollutants and Heavy Metalsmentioning
confidence: 99%
“…Compared to other macromolecules, polyamidoamine (PAMAM) dendrimers owing to the hyper‐branched and symmetric structure have more amine groups in their spherical structure. Hence, PAMAM is widely applied for the modification of hydrophilicity features and contaminated adsorption in the field of membrane technology 24–29 …”
Section: Introductionmentioning
confidence: 99%
“…Hence, PAMAM is widely applied for the modification of hydrophilicity features and contaminated adsorption in the field of membrane technology. [24][25][26][27][28][29] Also, chitosan is a natural polysaccharide, non-toxic and inexpensive, with adsorption capability on negative pregnant surfaces due to its polyelectrolyte nature in acidic areas as well as the ability to form a gel, thermal and chemical stability and antibacterial properties can be used as a coating for the MOF. The chitosan surface could be further functionalized due to the high presence of amino, hydroxyl and carboxyl groups.…”
Section: Introductionmentioning
confidence: 99%